Upaya Dinas Pemberdayaan Perempuan, Pengendalian Penduduk Dan Keluarga Berencana Dalam Penurunan Angka Stunting Di Kota Bengkulu - Mulistin, Elik; Nopianti, Heni; Himawati, Ika Pasca (Jayapangus Press, 2025)
Stunting is a serious health issue in Indonesia that affects the physical and cognitive development of children. The city of Bengkulu has shown a significant decline in stunting rates, from 22.2% in 2021 to 6.2% in 2024, through the implementation of various strategic programs. This study aims to analyze the efforts of the Women's Empowerment, Child Protection, Population Control, and Family Planning Agency (DP3AP2KB) in Bengkulu City to reduce stunting rates. This research employs a qualitative approach using descriptive methods through non-participant observation and semi-structured interviews. The technique for determining informants uses purposive sampling, with the main informant being staff from the DP3AP2KB involved in handling stunting. The research results show that key programs such as the Foster Parent for Stunting Children (BAAS), Peer Counseling for Adolescents (Koreya), Mini Workshops, and Stunting Case Audits have been implemented, to innovative strategies such as counseling and TPK orientation, as well as intensive assistance to pregnant women and toddlers through posyandu cadres. Collaborative efforts involving various sectors and the community have played a vital role in raising awareness about the importance of the First 1000 Days of Life. Despite challenges like limited funding and low awareness, the program serves as a national model for reducing stunting rates through cross-sector collaboration and community-focused initiatives.